If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(10m + 7) = 9(8m + 9) Reorder the terms: 9(7 + 10m) = 9(8m + 9) (7 * 9 + 10m * 9) = 9(8m + 9) (63 + 90m) = 9(8m + 9) Reorder the terms: 63 + 90m = 9(9 + 8m) 63 + 90m = (9 * 9 + 8m * 9) 63 + 90m = (81 + 72m) Solving 63 + 90m = 81 + 72m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-72m' to each side of the equation. 63 + 90m + -72m = 81 + 72m + -72m Combine like terms: 90m + -72m = 18m 63 + 18m = 81 + 72m + -72m Combine like terms: 72m + -72m = 0 63 + 18m = 81 + 0 63 + 18m = 81 Add '-63' to each side of the equation. 63 + -63 + 18m = 81 + -63 Combine like terms: 63 + -63 = 0 0 + 18m = 81 + -63 18m = 81 + -63 Combine like terms: 81 + -63 = 18 18m = 18 Divide each side by '18'. m = 1 Simplifying m = 1
| 5x+4=x+2 | | -9=-8+x | | 4.6x+2.2=29.8 | | 3.9=1.3-(4y) | | B=T-LcsolveT | | 14=7(x-1) | | 8x+4x-76=95-7x | | 5r+6r+7r-6= | | -0.01+0.1+(-1)+10= | | 5p+5=4p+12 | | 4t^2-24t-1=0 | | 3x+12=2x+72 | | 2(x+1)=10-2 | | 7x+146+x+48+65=65 | | 3+4-2+(8-5)= | | 3x-11=-33 | | t^2+16=8r | | -15+n=-25 | | 5x(12)-22+8x+46=180 | | 7e+3p+4p-5x+6= | | 1.9=-0.2 | | 5m-9n-6m=9n | | 29-4=-7(3x+8) | | 3x-2+19=180 | | x-(-2)=14 | | 7e+3p+4p-x+6= | | 15-4(3-x)=12+15x | | 14x-(3x-2)=90 | | 3.9=1.3-.4y | | x^2-sqrt(6)x+4=0 | | 15x+2x-8=0 | | 3+4-2(8-5)= |